Effect of Means of Problem-Oriented Physical Rehabilitation on Pain and Tactile Sensitivity and Pain Syndrome Intensity in Women with Post-Mastectomy Syndrome - Одинець, Т. Є.; Бріскін, Ю. А. (Physical Education Theory and Methodology, 2015)
The objective of the paper is to determine the effectiveness of problem-oriented physical rehabilitation of women with post-mastectomy syndrome in terms of normalization of their sensitivity and lessening of the pain syndrome. Materials and methods. The paper provides a review of the related literary sources and empirical data analyzed and summarized, offers definitions of pain by the Visual Analogue Scale, McGill Pain Questionnaire and the Verbal Rating Scale, evaluates tactile and pain sensitivity, and uses the methods of mathematical statistics. The participants in the study were 50 women with diagnosed with the post-mastectomy syndrome and at the stage of residential treatment. Results: The developed problem-oriented physical rehabilitation experimentally proved effective by showing improvements in tactile and pain sensitivity, and pain lessening by the sensory, affective and rating scales in women with post-mastectomy syndrome at the stage of residential treatment.